OPTIMASI LUASAN PETAK TEBANG DI HUTAN TANAMAN RAWA GAMBUT BERDASARKAN PRODUKTIVITAS DAN BIAYA - Sona Suhartana; Yuniawati; Dulsalam (Jurnal Penelitian Hasil Hutan, 2013)
As of this occasion, the management of timber harvesting at the peat-swamp plantation-forest in practice still has not yet reached the optimal tree felling plot area. Consequently, this necessitates exploring a representative model to determine meticulously such optimal plot area, thereby ensuring the forest management to proceed in a sustainable way. In relevant, the related study was carried out consecutively in May 2012 at the PT Wira Karya Sakti's concession area in Jambi; and in June 2012 at the PT Riau Andalan Pulp & Paper's concession area in Riau. For such, the necessary data were taken descriptively and purposively, which comprised the felling-plot areas (X) and the costs (Y) for skidding, maintenance, and canal erection. Further, the obtained X-Y data couples were analyzed for possible quadratic regression models. Results revealed that in Jambi the X-Y model came-up in the regression equation as Y =254.82 - 10.98 X + 0.21 X (R = 0.43 ), with the optimum felling area (X) equal to 26.69 ha and the minimum cost for skidding, maintenance, and canal erection (Y) reaching 105.32 (in Rp 1,000,000,000). Correspondingly, in Riau, the X-Y appeared as Y =299.47 - 14.85 X + 0.26 X (R = 0.59 ), with the optimum felling area (X) reaching 28.60 ha and the minimum cost (Y) as much as 87.14 (in Rp 1.000.000.000).